The Balkans as European Otherness. On Shaping Italian Public Opinion about the War in Croatia - Ivana Škevin; Iva Grgić Maroević ([sic])
In Croatia, the political changes involving most of Eastern Europe in the late 1980s and early 1990s included a war fought between 1991 and 1995. This paper aims, by examining the press releases and newspaper articles published in the Italian daily La Stampa in 1995, to show how this influential newspaper worked on shaping Italian public opinion about the war in Croatia, and to examine the extent to which well-rooted stereotypes about the Balkans played a role in the process. The application of the methods of Critical Discourse Analysis on the material has confirmed the occurrence of stereotypes expressed through several types of polarized representations, for example, the one between the good (Italy/Europe/West) and the bad (Croatia/the Balkans – associated with “primitive” nationalism and chaos). It has also shown that Italy (as part of Europe), largely saw itself as the “appointed” Western civilized neighbour towards one of its Balkan neighbours, Croatia, and worked on trying, as Todorova would put it, “to normalise” it.